Tailoring the Electroactive Area of Carbon Screen-Printed Electrodes by Simple Activation Steps Towards Rutin Determination - Aguirre-Quintana, M; Aguirre-Quintana, M (Springer Science and Business Media Deutschland GmbH, 2023)
Screen-printed electrodes (SPEs) have the advantage of being considered electrochemical cells that can be implemented in portable sensor applications. With the aim to improve the SPE performance, herein, we present different electrochemical surface modifications of carbon-based SPEs by cyclic voltammetry in hydrogen peroxide or sodium peroxide solution. SPEs were characterized using contact angle, Raman spectroscopy, laser-induced breakdown spectroscopy (LIBS), and electrochemical methods, including cyclic voltammetry (CV), electrochemical impedance spectroscopy, and square wave voltammetry (SVW). Main results agree with the observed changes by Raman spectroscopy and the sp2/sp3 ratio (I D/I G) of carbon vibrational bands. The diminishing of C2 Swan signal determined by LIBS suggests that the activation steps produced defects onto the working electrode in the SPE. Considering that the different intermolecular forces of the redox couples are useful to indirectly evaluate the different functional groups, the activated SPEs were studied in the presence of rutin and [Fe(CN)6]3−/[Fe(CN)6]4− redox couples. Main results show that the electrochemical response of the activated electrode surfaces can be properly used to improve the rutin electrochemical determination. Graphical Abstract: [Figure not available: see fulltext.] © 2023, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.